1980
DOI: 10.1111/j.1365-2125.1980.tb04816.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐individual differences in the glycine conjugation of salicylic acid [proceedings]

Abstract: debrisoquine orally on a non-treatment day. Two patients were phenotypically poor metabolisers, but the median metabolic ratio (1.4, range 0.5-10.7) of the extensive metabolisers was significantly (P < 0.01) greater than that of the untreated patients. There was no correlation between the metabolic ratio of an individual patient and the number of PUVA treatments received.We therefore conclude that debrisoquine 4-hydroxylation is not impaired in untreated psoriatic patients. PUVA therapy appears to inhibit debr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Gupta and coworkers (1975) found that steady-state serum salicylate concentrations were determined by the apparent rate of salicylurate formation. The age and sex influences on the formation of salicyluric acid might give rise to an explanation for the large inter-individual differences in glycine conjugation of salicylate found in Caldwell et al (1980) study. The present results further confirm the finding of a previous study on animals that higher salicylate concentrations in females is due to an intrinsically lower formation rate of salicyluric acid in this gender (Sechserova et al, 1975).…”
Section: Discussionmentioning
confidence: 97%
“…Gupta and coworkers (1975) found that steady-state serum salicylate concentrations were determined by the apparent rate of salicylurate formation. The age and sex influences on the formation of salicyluric acid might give rise to an explanation for the large inter-individual differences in glycine conjugation of salicylate found in Caldwell et al (1980) study. The present results further confirm the finding of a previous study on animals that higher salicylate concentrations in females is due to an intrinsically lower formation rate of salicyluric acid in this gender (Sechserova et al, 1975).…”
Section: Discussionmentioning
confidence: 97%
“…Salicylates are excreted mainly by the kidney as salicyluric acid (75%), free salicylic acid (10%), salicylic acid phenolic glucuronide (10%), salicylic acid acyl glucuronide (5%), and gentisic acid (<1%). The elimination half-life of SA is about 2 to 3 h (Cummings et al, 1966;Caldwell et al, 1980;Spiller et al, 2000;Emudianughe et al, 1986). T max , the required time to reach C max , for SA is approximately 60 min (Kiang et al, 2006).…”
mentioning
confidence: 99%
“…The salicyluric acid, which is the glycine conjugate, is the most abundant metabolite in the urine of individuals who received a therapeutic dose of SA. The glucuronide conjugates of SA, that is, salicylic acid phenolic glucuronide (SAPG) and salicylic acid acyl glucuronide (SAAG) (Caldwell et al, 1980;Cummings et al, 1966), represent between 0.8 and 42% of the administered dose (Hutt et al, 1986). Small amounts of SA are hydroxylated to gentisic acid.…”
mentioning
confidence: 99%